An Examination of the Flora and pH Changes in the External Auditory Canal in Patients with Seborrheic Dermatitis - Topal, Olgun; Kars, Ayhan; Topal, Kübra; Atalay, Fatma; Üçüncü, Harun (LookUs Bilisim A.S., 2023)
Aim: To investigate flora and pH changes in the external auditory canal (EAC) in patients with seborrheic dermatitis (SD).Material and Method: Twenty-five patients with SD presenting to the Ataturk University Faculty of Medicine Ear, Nose and Throat and Dermatology Departments and 20 healthy controls were included in this prospective study. All individuals’ EAC floras were collected using culture swabs, and EAC pH was measured using a surface pH meter.Results: Coagulase-negative staphylococci and diphtheroid bacilli, representing normal flora elements, grew in 15 patients in the SD group and 10 in the healthy control group. pH values in the SD patient group ranged between 4.17 and 4.89, with a mean value of 4.47±0.2. pH values among the healthy controls ranged between 4.33 and 4.94, with a mean value of 4.63±0.2.Conclusion: SD did not affect EAC flora or EAC pH values
Keywords: Otorhinolaryngology; external auditory canal flora; external auditory canal pH; seborrheic dermatitis; Kulak Burun Boğaz; 3. Good health